THE PERMIAN BIOSTRATIGRAPHY OF THE KOLYMA-OMOLON REGION, NORTHEAST ASIA - Ganelin V.G.; Biakov A.S. (My University, 2006)
The main features of the tectonics, Permian paleogeography, biota, structural-facies zonation of the Kolyma-Omolon region are analysed. The characteristics of the Permian regional stratigraphic scale of the Kolyma-Omolon region are described. The Permian deposits of the Kolyma-Omolon region are divided into four regional stratigraphic subdivisions, ranked as superhorizons, which in turn are subdivided into nine horizons. These horizons are further subdivided into 18 provincial zones ('lones' in accordance with Russian stratigraphical nomenclature). Most of the lones distinguished have dual index species, representing the dominant brachiopod and bivalve species. The chosen nominal species of these lones are, as a rule, related to each other phylogenetically, and as such they represent key stages in the evolution of their respective taxonomic groups through the Permian. The resultant biostratigraphic scale is adopted as a regional one for the Kolyma-Omolon, Chukotka, and southeastern part of the Verkhoyan-Okhotsk regions. Almost all the lones distinguished can also be recognized in the Verkhoyansk region, and many of the lones are also traceable outside Northeast Asia. © 2006 Elsevier Ltd. All rights reserved.
Keywords: BIVALVES; BRACHIOPODS; FORAMINIFERS; KOLYMA-OMOLON REGION; NORTHEAST ASIA; PERMIAN; Paleozoic::Permian; Палеозой::Пермская